2019
DOI: 10.1093/jscr/rjz340
|View full text |Cite
|
Sign up to set email alerts
|

Isolated pneumomediastinum following laparoscopic cholecystectomy: a rare complication

Abstract: Development of postoperative pneumomediastinum is one of the most infrequent complications of laparoscopic procedures. We report a case of a 47-year-old woman who developed pneumomediastinum consequently to laparoscopic cholecystectomy. The patient was treated conservatively and was discharged on the fifth postoperative day. Early detection of this condition, differential diagnosis and careful monitoring of the patient are important, as it may lead to severe consequences, including the life-threatening tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…However, routine chest x- ray can be utilized to monitor the resolution and tissue absorption of PM [ 6 , 12 ]. Despite the high solubility of CO 2 in blood, many studies had observed that extra abdominal gas could persist from 1 to 4 days after surgery till complete resolution, it is believed this might be due to the avascular nature of the areolar tissue of the mediastinum [ 6 , [13] , [14] , [15] ]. In our patient, the initial portable chest x-ray was suspicious for PM and the repeated x-ray in post-operative day 2 did not show any concern compared to the intra-operative one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, routine chest x- ray can be utilized to monitor the resolution and tissue absorption of PM [ 6 , 12 ]. Despite the high solubility of CO 2 in blood, many studies had observed that extra abdominal gas could persist from 1 to 4 days after surgery till complete resolution, it is believed this might be due to the avascular nature of the areolar tissue of the mediastinum [ 6 , [13] , [14] , [15] ]. In our patient, the initial portable chest x-ray was suspicious for PM and the repeated x-ray in post-operative day 2 did not show any concern compared to the intra-operative one.…”
Section: Discussionmentioning
confidence: 99%
“…In adult literature, PM had been reported in some laparoscopic procedures such as cholecystectomy, hysterectomy and herniorraphy [ [13] , [14] , [15] , [16] ]. Other studies looked at the incidence and significance of PM after laparoscopic surgery related to esophagus and found that two thirds of their patients had developed PM that spontaneously resolved the next day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of choice for symptomatic cholelithiasis has become laparoscopic cholecystectomy [ 1 ]. Laparoscopic surgeries have gained wide acceptance in our time due to the reduced morbidity and mortality, shorter hospital stay, better postoperative recovery, less postoperative pain, and reduced cost as compared to open surgeries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%